PERANCANGAN SOLAR IRRIGATION PUMP DENGAN SISTEM SOLAR TRACKER DI SUBAK MALIKODA - Windradharama W., A.A. G. Guna; Satya Kumara, I Nyoman; Setiawan, I Nyoman (Program Studi Teknik Elektro UNUD, 2023)
Water is a fundamental necessity for agricultural land and can be obtained from various sources depending on its geographical location. The Keliki Village Farmers Group in Subak Malikoda faces the challenge of drought, leading to a shortage of water supply during the dry season. In this research, the Solar Irrigation Pump (SIP) is designed with a solar tracker system to pump groundwater with the aim of enhancing irrigation water supply for Subak Malikoda during the dry season. The design of the solar-powered irrigation pump system consists of an 18.5 kW submersible pump coupled with a 23.1 kWp PV system using 60 monocrystalline solar modules equipped with a solar tracker and utilizing a 30 kW inverter. Based on the conducted analysis, the PVSyst results show that the SIP without a solar tracker can operate for 6,067 hours with an average water discharge of 274.9 m3/day, based on the received global effective irradiation of 1765.1 kWh/m2 in one year. However, with the use of the solar tracker system, the pump can operate for 6,933 hours with a water discharge of 305.2 m3/day and global effective irradiation of 1963.8 kWh/m2 in one year. The results of the analysis conclude that the SIP with a solar tracker system is capable of operating optimally and meeting the water discharge requirements of Subak Malikoda. This positions the solar tracker system as an effective solution in enhancing the water supply for Subak Malikoda during the dry season.